Novel peptides derived from αs1-casein with opioid activity and mucin stimulatory effect on HT29-MTX cells. (August 2016) - Fernández-Tomé, S.; Martínez-Maqueda, D.; Girón, R.; Goicoechea, C.; Miralles, B.; Recio, I.
Highlights: 144 YFYPEL 149 and 144 YFYPE 148 demonstrated opioid activity on guinea pig ileum. 144 YFYPEL 149 and 144 YFYP 147 presented different behaviour against opioid receptor. 144 YFYPEL 149 was the minimum fragment with stimulatory effect on MUC5AC expression. Abstract: The opioid effect of αs1 -casein fragments related to 143 AYFYPEL 149 and 144 YFYPEL 149, which had previously shown mucin-stimulatory activity in human goblet cells, was investigated. Peptides 144 YFYPEL 149 and 144 YFYPE 148 showed opioid agonistic activity in guinea pig ileum, and in mouse vas deferens but to a lower extent. Peptides were partly hydrolysed during the assay and several of the resulting fragments lost the N-terminal Tyr residue. Docking of peptides 144 YFYPEL 149 (active) and 144 YFYP 147 (inactive) into the active site of the opioid receptor model showed remarkable differences regarding the flexibility at the third intracellular loop of the receptor and the interaction with Pro at the peptide C-terminus that forced residues Arg 148 and Glu 166 from the receptor to move towards the interior of the binding pocket. The study on human cells HT29-MTX has shown that 144 YFYPEL 149 is the minimum fragment able to stimulate MUC5AC expression.